2022
DOI: 10.3390/genes13112152
|View full text |Cite
|
Sign up to set email alerts
|

miR-9 and miR-181a Target Gab2 to Inhibit the Proliferation and Migration of Hepatocellular Carcinoma HepG2 Cells

Abstract: The incidence of liver cancer ranks seventh globally, with nearly half of all cases occurring in East Asia, but currently, there are very few drugs to treat it. Our previous studies demonstrated that the signal integration protein Gab2 is a potential drug target for the prevention and therapy of liver cancer. Here, we screened for and identified two miRNAs that target Gab2 to suppress the proliferation and migration of hepatocellular carcinoma (HCC) cells. First, we predicted Gab2-targeting miRNAs through biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…miR‐9 can target the signalling integrin Gab2 to inhibit the proliferation and migration of HCC cells. 117 miR‐9 upregulation can inhibit ANO1 expression, 103 but whether miR‐9 further inhibits cell proliferation and migration in HCC through ANO1 still needs further investigation. Ferroptosis is a key cell death response triggered upon treatment of multiple tumours.…”
Section: Pathologic Role Of Ano1 In the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐9 can target the signalling integrin Gab2 to inhibit the proliferation and migration of HCC cells. 117 miR‐9 upregulation can inhibit ANO1 expression, 103 but whether miR‐9 further inhibits cell proliferation and migration in HCC through ANO1 still needs further investigation. Ferroptosis is a key cell death response triggered upon treatment of multiple tumours.…”
Section: Pathologic Role Of Ano1 In the Livermentioning
confidence: 99%
“…This finding suggested that diltiazem might play a role in the treatment of HCC, but further experimental studies are needed. miR‐9 can target the signalling integrin Gab2 to inhibit the proliferation and migration of HCC cells 117 . miR‐9 upregulation can inhibit ANO1 expression, 103 but whether miR‐9 further inhibits cell proliferation and migration in HCC through ANO1 still needs further investigation.…”
Section: Pathologic Role Of Ano1 In the Livermentioning
confidence: 99%